A Kv7.2 mutation associated with early onset epileptic encephalopathy with suppression‐burst enhances Kv7/M channel activity. (31st March 2016) - Devaux, Jérôme; Abidi, Affef; Roubertie, Agathe; Molinari, Florence; Becq, Hélène; Lacoste, Caroline; Villard, Laurent; Milh, Mathieu; Aniksztejn, Laurent
Summary: Mutations in the KCNQ2 gene encoding the voltage‐gated potassium channel subunit Kv7.2 cause early onset epileptic encephalopathy (EOEE). Most mutations have been shown to induce a loss of function or to affect the subcellular distribution of Kv7 channels in neurons. Herein, we investigated functional consequences and subcellular distribution of the p.V175L mutation of Kv7.2 (Kv7.2 V175L ) found in a patient presenting EOEE. We observed that the mutation produced a 25–40 mV hyperpolarizing shift of the conductance–voltage relationship of both the homomeric Kv7.2 V175L and heteromeric Kv7.2 V175L /Kv7.3 channels compared to wild‐type channels and a 10 mV hyperpolarizing shift of Kv7.2 V175L /Kv7.2/Kv7.3 channels in a 1:1:2 ratio mimicking the patient situation. Mutant channels also displayed faster activation kinetics and an increased current density that was prevented by 1 μm linopirdine. The p.V175L mutation did not affect the protein expression of Kv7 channels and its localization at the axon initial segment. We conclude that p.V175L is a gain of function mutation. This confirms previous observations showing that mutations having opposite consequences on M channels can produce EOEE. These findings alert us that drugs aiming to increase Kv7 channel activity might have adverse effects in EOEE in the case of gain‐of‐function variants.